PERANCANGAN BRANDING MEDIA PROMOSI FASHION TRADISIONAL-MODERN (Studi Kasus : Wenny Chang) - Hubert, Hubert; Yonatia, Jessica; Susanti, Elizabeth (Universitas Mercu Buana, 2024)
The development of the fashion industry in Indonesia has provided interesting opportunities for designers to combine modern designs with traditional elements that can help preserve local culture. This research aims to design a promotion strategy for Wenny Chang, a fashion designer who is well-known for her work in major cities in Indonesia. Wenny Chang's distinctive feature is her use of traditional Indonesian fabrics harmoniously combined with other materials, with a modern touch. Each of Wenny Chang's works has a unique and beautiful traditional-modern characteristic. This research will use a qualitative approach with a case study method to study every small detail of Wenny Chang's work, resulting in integrated data. The research will also produce a promotional media design strategy tailored to the needs and characteristics of Wenny Chang and potential consumer preferences. The results of Wenny Chang's promotional media designs include: brand identity, business suite, souvenirs, fashion photography, and fashion videography. This research aims to contribute to the domestic fashion industry practitioners in strengthening their brand through the selection of appropriate promotional media, expanding markets, and increasing public appreciation for traditional Indonesian fabrics.